Certificate of Accreditation for Master of Advanced Information Technology - Universiti Malaysia Sarawak (Universiti Malaysia Sarawak (UNIMAS), 2013)
Certificate of Accreditation for Master of Advanced Information Technology has attained the quality assurance standards set by the agency and is in compliance with the Malaysian qualifications framework Level 7. Date of Accreditation : 11/09/2013